Influence of ethnic origin on the clinical characteristics and intestinal flora of irritable bowel syndrome: a prospective study between Han and Tibetan patients - Ma, Xiao; Huan, Hui; Liu, Chao; Hu, Hong; Ren, Tao (Frontiers in Medicine, 2024)
Background Few studies have focused on the clinical characteristics and intestinal flora of Tibetan patients with irritable bowel syndrome (IBS). The study aimed to compare the difference of between Tibetan and Han patients with IBS. Methods Patients who met inclusion and exclusion criteria were divided into the Tibet and Han groups. A simplified Gastrointestinal Symptom Rating Scale (GSRS)-based questionnaire was used to assess the IBS severity. Fecal samples from all subjects were collected for the analysis of gut microbiota using 16sRNA Illumina sequencing. Results No significant difference was found in the total symptom scores between two groups. However, Tibetans with IBS are more prone to bloating than Hans (17.41% vs 9.09%, p < 0.001). A profit shift in the gut microbiota was shown between the two groups. The ratio of Firmicutes/Bacteroidetes was significantly lower in the Tibet group than in the Han group (2.954 ± 0.78 vs 8.23 ± 2.04, p = 0.004). In the Tibet group, the level of the genus Blautia decreased significantly compared to the Han group, and there was a significant negative correlation between the level of Blautia and the bloating scores (Pearson r = −0.33, p = 0.025). Conclusion The characteristics of Tibetan patients differ from those of Han patients with IBS, not only in terms of the clinical symptoms, but also in the characteristics of intestinal flora. Tibetans with IBS are more prone to bloating, which might be due to the different gut microbiota. The genus Blautia may play a role in this mechanism.